Gemmatimonas groenlandica sp. nov. Is an Aerobic Anoxygenic Phototroph in the Phylum Gemmatimonadetes - Zeng, Yonghui; Nupur,; Wu, Naicheng; Madsen, Anne Mette; Chen, Xihan; Gardiner, Alastair T.; Koblížek, Michal (Frontiers in Microbiology, 2021)
The bacterial phylum Gemmatimonadetes contains members capable of performing bacteriochlorophyll-based phototrophy (chlorophototrophy). However, only one strain of chlorophototrophic Gemmatimonadetes bacteria (CGB) has been isolated to date, hampering our further understanding of their photoheterotrophic lifestyle and the evolution of phototrophy in CGB. By combining a culturomics strategy with a rapid screening technique for chlorophototrophs, we report the isolation of a new member of CGB, Gemmatimonas (G.) groenlandica sp. nov., from the surface water of a stream in the Zackenberg valley in High Arctic Greenland. Distinct from the microaerophilic G. phototrophica strain AP64T, G. groenlandica strain TET16T is a strictly aerobic anoxygenic phototroph, lacking many oxygen-independent enzymes while possessing an expanded arsenal for coping with oxidative stresses. Its pigment composition and infra-red absorption properties are also different from G. phototrophica, indicating that it possesses a different photosystem apparatus. The complete genome sequence of G. groenlandica reveals the unique and conserved features in the photosynthesis gene clusters of CGB. We further analyzed metagenome-assembled genomes of CGB obtained from soil and glacier metagenomes from northeast Greenland, revealing a wide distribution pattern of CGB beyond the stream water investigated. Originality/Importance The bacterial phylum Gemmatimonadetes is an important but yet understudied group in natural microbial communities. The isolation of the only phototrophic member of this phylum, Gemmatimonas phototrophica, was reported in 2014, which expanded the list of known bacterial phyla capable of performing photosynthesis. Since then, no new phototrophic member of this phylum has been isolated. By applying a novel isolation strategy of combining a mass spectroscopy-based high-throughput profiling method and a rapid screening technique for phototrophic bacterial colonies, we successfully isolated the second phototrophic member of this phylum, Gemmatimonas groenlandica, from a stream in Northeast Greenland. Its discovery confirms the widespread presence of phototrophic Gemmatimonadetes bacteria in the environment and raises an intriguing question on the evolutionary history of phototrophy in the phylum Gemmatimonadetes. Distinct from the microaerophilic slow growth rate evident with G. phototrophica, G. groenlandica is a strict aerobe and can be readily cultured in liquid medium, opening new possibilities for future strain genetic engineering and detailed photophysiological studies.